Effect of experimental stress on the small bowel and colon in healthy humans. Issue 4 (20th February 2015) - Pritchard, S. E.; Garsed, K. C.; Hoad, C. L.; Lingaya, M.; Banwait, R.; Thongborisute, W.; Roberts, E.; Costigan, C.; Marciani, L.; Gowland, P. A.; Spiller, R. C.
Abstract: Background: Symptoms of irritable bowel syndrome (IBS) are frequently reported to be exacerbated by stress. Animal studies suggest that corticotrophin releasing hormone (CRH) mediates the effect of stress on the bowel. We have shown that stressed IBS patients with diarrhea have constricted small bowels. We hypothesized that we could mimic this effect by applying experimental stress in the form of either hand immersion in ice water or CRH injection in healthy volunteers (HV). Methods: The postprandial effect of the cold pressor test (repeated hand immersion in ice cold water) and injection of CRH, were assessed vs control in two groups of 18 HVs. Key Results: CRH produced a significant rise from baseline salivary cortisol levels ( p = 0.004) not seen with the cold pressor test. Small bowel water content (SBWC) fell postprandially on all four treatments. SBWC was significantly reduced by both stressors but CRH caused a greater effect (anova, p < 0.003 vs p = 0.02). Ascending colon (AC) volume was greater after CRH injection compared with saline ( p = 0.002) but no differences were seen with the cold pressor test vs warm water. Postprandial increase in colon volume was also reduced by CRH which also increased the sensations of distension and bloating. Conclusions & Inferences: Two experimental stressors were shown to constrict the small bowel, mimicking the effect previously seen in IBS‐D patients. CRH increased the volume of the AC. We speculate that stress accelerates transfer of water from the small bowel to the AC. Abstract : View the podcast on this paper at the following sites: Youtube:https://www.youtube.com/watch?v=UiW_cJp6nGA iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility/id976042116 Previous MRI studies have shown that IBS patients with diarrhea have constricted small bowels. This study, on healthy volunteers, showed that cortisol releasing hormone (CRH) injections and cold water hand immersion stress constricted the small bowel and CRH also increased the volume of the ascending colon. This was associated with sensations of distension and bloating and increased CRH release could be the mechanism whereby psychological stress contributes to diarrhea in some patients.